Assessment of genetic diversity and phylogenetic relationship of Limousin herds in Hungary using microsatellite markers - Márton Szűcs; Ferenc Szabó; Beáta Bán; Csilla Józsa; László Rózsa; Attila Zsolnai; István Anton (Asian-Australasian Journal of Animal Sciences, 2019)
Objective This study was conducted to investigate basic information on genetic structure and characteristics of Limousin population in Hungary. Obtained results will be taken into consideration when adopting the new breeding strategy by the Association of Hungarian Limousin and Blonde d’Aquitaine Breeders (AHLBB). Methods Genetic diversity and phylogenetic relationship of 3,443 Limousin cattle from 16 different herds were investigated by performing genotyping using 18 microsatellite markers. Amplified DNA was genotyped using an automated genetic analyzer. Results Mean of effective alleles (ne) of the populations was 3.77. Population C had the lowest number of effective alleles (3.01) and the lowest inbreeding coefficient (FIS) value (−0.15). Principal component analysis of estimated genetic distance (FST) values (p<0.000) revealed two herds (C and E) distinct from the majority of other Limousin herds. The pairwise FST values of population C compared to the others (0.066 to 0.120) fell into the range of moderate genetic distance: 0.050 to 0.150, while population E displayed also moderate genetic distance (FST values in range 0.052 to 0.064) but only to six populations (G, H, J, L, N, and P). FST(C-E) was 0.148, all other pairs -excluding C and E herds- displayed low genetic distance (FST<0.049). Population D, F, I, J, K, L, N, O, and P carried private alleles, which alleles belonged to 1.1% of the individuals. Most probable number of clusters (K) were 2 and 7 determined by Structure and BAPS software. Conclusion This study showed useful genetic diversity and phylogenetic relationship data that can be utilized for the development of a new breeding strategy by AHLBB. The results presented could also contribute to the proper selection of animals for further whole genome scan studies of Limousins.